THE REFLECTIONS THAT THE PRACTICE OF SLAVE LABOR LEFT IN BRAZIL OF SECÚLO XXI: A CONSTANT STRUGGLE OF BRAZILIAN LEGISLATION AGAINST SOCIAL PRIMITIVISM (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Slavery in Brazil, in a legal way, lasted for many. Only after years of fighting has it been sanctioned a law prohibiting its practice. However, slavery continued to be clandestinely exercised in the country and its practice spreads to the present day, since its culture is still predominant. Despite some advances in terms of labor laws, slave labor continues to be exercised in contemporary Brazil causing enormous violations of rights and guarantees that the worker has acquired over the centuries. Although there are laws in the national and international spheres that prohibit the practice of slave labor and which has punishment for those who commit such an act, it continues to exist. Thus, it is to ask what reflections the practice of slave labor has left in Brazil of the 21ST century. To this end, the present work will be carried out through the use of the deductive approach method and methods of historical, comparative and bibliographical procedure. The justification of the theme is due to an informative bias to society, since although slave labor has been abolished for more than a century, its practice is still common.